-c-5=c+93

Simple and best practice solution for -c-5=c+93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -c-5=c+93 equation:


Simplifying
-1c + -5 = c + 93

Reorder the terms:
-5 + -1c = c + 93

Reorder the terms:
-5 + -1c = 93 + c

Solving
-5 + -1c = 93 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
-5 + -1c + -1c = 93 + c + -1c

Combine like terms: -1c + -1c = -2c
-5 + -2c = 93 + c + -1c

Combine like terms: c + -1c = 0
-5 + -2c = 93 + 0
-5 + -2c = 93

Add '5' to each side of the equation.
-5 + 5 + -2c = 93 + 5

Combine like terms: -5 + 5 = 0
0 + -2c = 93 + 5
-2c = 93 + 5

Combine like terms: 93 + 5 = 98
-2c = 98

Divide each side by '-2'.
c = -49

Simplifying
c = -49

See similar equations:

| 2.5a=5(1.25)12.50 | | n-65=-n-9 | | 1n+2n= | | x-59=-x-9 | | f(-5)=2x+3 | | y=.10x+2.40 | | -b+8=b+54 | | c+82=-c+4 | | x^2-72x-89=0 | | x^2-882x-98=0 | | 5x+10y=20+5y | | 5y+10x=20+5x | | X+x+5=15334 | | -2=7t | | 34+72=2 | | 2(x)+3-6=10-x | | 2(3x-7)=4(3x+2)+6(5x+9)+3 | | 9y-32=-4(y-5) | | 4(w+3)=6w+24 | | 9y-37=5(y-9) | | 4x+9x-8x-5x=15 | | y=11+-5x | | 3(x-6)=39 | | 8-(6-6n)+9n=-2+12(n+1) | | (m^2+6m+4)(3m-1)=0 | | 9y^2+2+16=-24y | | 2x+6-x=(3x+18) | | 9y^22+16=-24y | | (w-9)*(w+4)= | | (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 |

Equations solver categories